The Similarity in the Holy Quran (Journal of the College of Education for Women, 2019)
The method of Similarity of important topics in Arabic Rhetoric has ample evidence in the Qur'an and the Hadith and the words of the Arabs and this study is limited to only the Koran.There have been Similarity in the Holy Quran on both types : investigative and discretion , but the verses are more Similarity investigative and in verse 49 Similarity investigative and in verse 25.The rush of Albulageyen and many other examples of Quranic Vmtheloa on Similarity , with a linguistic analysis and return to the origins of the meanings are not properly counted Similarity , Kolvaz cunning , deception , and maliciousness , the bad and ridicule.This study seeks as much as possible to the statement of this phenomenon and stand on these thorny issues and address the correct destination and strong evidence to refute the arguments of Albulageyen in it. Find map consists of an introduction and two sections talking about the first topic Similarity language , and idiomatically , and the relationship of Similarity Batabaq , and alliteration , and whether the problem Mohsen moral or verbal ? . Then talking about the second topic Similarity two types of investigative and discretion and applications in the Koran. Then keeping conclusion with the conclusion reached by the researcher.Then the index detailed Similarity verses in the Koran, then newspaper sources and references for this search .